2023
DOI: 10.1002/smll.202302998
|View full text |Cite
|
Sign up to set email alerts
|

Microwell Confined Electro‐Coalescence for Rapid Formation of High‐Throughput Droplet Array

Abstract: Droplet array is widely applied in single cell analysis, drug screening, protein crystallization, etc. This work proposes and validates a method for rapid formation of uniform droplet array based on microwell confined droplets electro‐coalescence of screen‐printed emulsion droplets, namely electro‐coalescence droplet array (ECDA). The electro‐coalescence of droplets is according to the polarization induced electrostatic and dielectrophoretic forces, and the dielectrowetting effect. The photolithographically fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Sun [ 72 ] reported that the simple pre-deposition of an ethanol layer enabled a series of procedures, including homogenization, solvent exchange, post-stretching, and air drying, thereby uniformly depositing densely structured graphene nanosheets and effectively limiting and eliminating the coffee-ring effect during inkjet printing, as shown in Figure 7 b. Inkley [ 73 ] successfully used triethylene glycol for pre-wetting the powder bed before printing, significantly expanding the range of droplet spacing to produce continuous lines, as shown in Figure 7 c. Duan [ 74 ] significantly altered the fluid drying kinetics by adding surfactants during solution printing and increasing the contact-line friction between the aqueous solution and the underlying non-wetting organic crystalline film. As a result, centimeter-level highly-arranged arrays of organic crystals were successfully prepared on different substrates, as shown in Figure 7 d. Liu [ 75 ] reacted large-scale droplet arrays with controlled curvature by selectively modifying the surface using tunable oxygen plasma, promoting precise patterns by adjusting chemical contrast; they also used droplet dosage modification to achieve precise adjustment, as shown in Figure 7 e. Feng [ 76 ] proposed and verified an efficient, high-throughput method for the rapid preparation of uniform droplet arrays induced by an electric field in multiple emulsion droplets within micropores. Polydisperse emulsions were prepared through mechanical stirring and then filling them into hydrophobic micropores through screen printing.…”
Section: Control Methods For Droplet Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun [ 72 ] reported that the simple pre-deposition of an ethanol layer enabled a series of procedures, including homogenization, solvent exchange, post-stretching, and air drying, thereby uniformly depositing densely structured graphene nanosheets and effectively limiting and eliminating the coffee-ring effect during inkjet printing, as shown in Figure 7 b. Inkley [ 73 ] successfully used triethylene glycol for pre-wetting the powder bed before printing, significantly expanding the range of droplet spacing to produce continuous lines, as shown in Figure 7 c. Duan [ 74 ] significantly altered the fluid drying kinetics by adding surfactants during solution printing and increasing the contact-line friction between the aqueous solution and the underlying non-wetting organic crystalline film. As a result, centimeter-level highly-arranged arrays of organic crystals were successfully prepared on different substrates, as shown in Figure 7 d. Liu [ 75 ] reacted large-scale droplet arrays with controlled curvature by selectively modifying the surface using tunable oxygen plasma, promoting precise patterns by adjusting chemical contrast; they also used droplet dosage modification to achieve precise adjustment, as shown in Figure 7 e. Feng [ 76 ] proposed and verified an efficient, high-throughput method for the rapid preparation of uniform droplet arrays induced by an electric field in multiple emulsion droplets within micropores. Polydisperse emulsions were prepared through mechanical stirring and then filling them into hydrophobic micropores through screen printing.…”
Section: Control Methods For Droplet Printingmentioning
confidence: 99%
“…( f ) ECDA chip-manufacturing process schematic: photolithography of micropores on ITO glass coated with Hyflon, emulsion filling, chip assembly and sealing, and micropore-constrained droplet electropolymerization. Reproduced with permission from [ 76 ], published by John Wiley and Sons, 2023. ( g ) Photography image of the PC sensor with different colors of PC dots.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication of the microfluidic chip was carried out using a standard soft lithography process. Initially, a uniform layer of negative photoresist (SU8-2050, Microchem, Westborough, MA, USA) with a height of 20 μm was spin-coated onto a 5 in. silicon wafer.…”
Section: Methodsmentioning
confidence: 99%